Nach dem Deutschstudium in Afrika wird man – was? Eine Überprüfung der Zielsetzungen der Deutschabteilung der Universität Lomé anhand einer Verbleibstudie - Hamann, Eva (Stellenbosch Papers in Linguistics Plus, 2009)
This paper reports on an investigation of the value of German Studies in eventual employment of students in this field. The objectives of German Studies in Africa have to include an indication of how inclusion in the curriculum is legitimized. Three approaches towards legitimization have developed since the establishment of German Departments at African Universities, namely (i) German Studies with a view to research and epistemological science, (ii) German in intercultural studies, and (iii) career-oriented German language learning. In this paper the implementation of these approaches will be examined on the basis of the objectives set out by the German Department at the University of Lomé. This will be done by discussing the results of a survey on the professional whereabouts of Togolese German Studies graduates to demonstrate the extent to which the objectives of the various approaches have been met. The paper concludes with a discussion of the implications of the findings for the programmes of the German Department at the University of Lomé.